2021
DOI: 10.1021/acsaelm.1c00424
|View full text |Cite
|
Sign up to set email alerts
|

Extended Compositional Range for the Synthesis of SWIR and LWIR Ge1–ySny Alloys and Device Structures via CVD of SnH4 and Ge3H8

Abstract: A chemical vapor deposition (CVD) strategy is presented for the synthesis of Ge1–y Sn y alloys on Si wafers with band gaps in the short-wave infrared (SWIR) range of 1.8–2.6 μm, as well as in the long-wave infrared (LWIR) at 12 μm and beyond. This broad compositional versatility is achieved by CVD reactions of Ge3H8 and SnH4 as Ge and Sn precursors, respectively. The use of conventional SnH4 instead of the previously used SnD4 is found to be critical in synthesizing alloys with Sn contents between 30 and 36%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Extrapolating to a fully strained film with 20% Sn, the strain would reach a value of −2.7%, which is unrealistic and would likely result in a catastrophic relaxation that renders the sample unsuitable for optical applications. This phenomenology is analogous to that observed in the case of Ge 1– y Sn y /Ge, where the high strain is the limiting factor for the incorporation of ever higher Sn fractions . The solution in that case was to forego the Ge buffer and grow directly on Si, and we adopt a similar strategy here.…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolating to a fully strained film with 20% Sn, the strain would reach a value of −2.7%, which is unrealistic and would likely result in a catastrophic relaxation that renders the sample unsuitable for optical applications. This phenomenology is analogous to that observed in the case of Ge 1– y Sn y /Ge, where the high strain is the limiting factor for the incorporation of ever higher Sn fractions . The solution in that case was to forego the Ge buffer and grow directly on Si, and we adopt a similar strategy here.…”
Section: Resultsmentioning
confidence: 99%
“…Our solution-based routes to Sn metal provides alternatives to known gas/vapor phase methods, such as the use of SnH 4 in the formation of tin-containing materials by chemical vapor deposition. 2,9…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies have reported that the performance of GeSn PDs is comparable, and can be even superior to that of the current commercially available semiconductor MIR PDs, 24,25 which make it a promising candidate for low-cost practical applications. Despite the limited solubility of Sn in Ge of ∼1%, 27,28 the recent advancements in low-temperature growth techniques using molecular beam epitaxy (MBE), 27,28 chemical vapor deposition (CVD), [29][30][31] and sputter 32 have enabled the growth of high-quality GeSn layers on Si or silicon-on-insulator (SOI) substrates, which can yield Sn contents up to 36%. 30 Various GeSn-based PDs have been demonstrated with an extended photodetection range, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] attaining up to 3.7 µm 47 and enhanced quantum efficiency, which highlights their potential for efficient MIR photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited solubility of Sn in Ge of ∼1%, 27,28 the recent advancements in low-temperature growth techniques using molecular beam epitaxy (MBE), 27,28 chemical vapor deposition (CVD), [29][30][31] and sputter 32 have enabled the growth of high-quality GeSn layers on Si or silicon-on-insulator (SOI) substrates, which can yield Sn contents up to 36%. 30 Various GeSn-based PDs have been demonstrated with an extended photodetection range, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] attaining up to 3.7 µm 47 and enhanced quantum efficiency, which highlights their potential for efficient MIR photodetection. However, the epitaxy of GeSn layers on Si or SOI substrates typically requires an appropriate buffer (usually Ge) to improve the material quality and induces an indispensable biaxial compressive strain.…”
Section: Introductionmentioning
confidence: 99%